Silver nanoparticles as a solid sorbent in ultrasound-assisted dispersive micro solid-phase extraction for the atomic absorption spectrometric determination of mercury in water samples. Issue 11 (30th September 2015) - Krawczyk, Magdalena; Stanisz, Ewa
Abstract : In this study, the analytical potential of USA DMSPE with silver nanoparticles as a solid sorbent combined with high-resolution continuum source ETAAS in the determination of mercury was evaluated. Abstract : The combination of ultrasound-assisted dispersive micro solid-phase extraction (USA DMSPE), with the use of silver nanoparticles (AgNPs) as a solid sorbent, with high-resolution continuum source electrothermal atomic absorption spectrometry (HR-CS ETAAS) is proposed for the preconcentration and determination of Hg 2+ ions in water samples. The main extraction and detection parameters were investigated. Effective preconcentration of trace mercury was achieved at pH 3.5 with 10 mg of AgNPs. Amalgamated mercury was dissolved in 200 μL of 7 mol L −1 HNO3 before atomic absorption spectrometry (AAS) detection. The concentration limit of detection was 0.005 ng mL −1 . The achieved preconcentration factor was 15 and the relative standard deviations (RSDs, %) for real water samples were 6–11%. The accuracy of this method was evaluated by analyses of CRMs. The method has been successfully applied to the determination of mercury in three different real water samples.